IRCULAR ECONOMY THROUGH INTEGRATING INDUSTRY 4.0: SUSTAINABLE TRANSFORMATION VIA IOT AND AI - NECULA ADINA-THEODORA; TĂNASE ANDREEA GABRIELA; MĂLDĂREANU ANDREEA; CREȚU RALUCA-FLORENTINA; BANȚA VIOREL COSTIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Business and production systems can embrace the circular economy’s principles if they are combined with advanced technologies from the Fourth Industrial Revolution — Industry 4.0. This paper discusses and shows how deployment of the IoT, AI and analytics technologies resolves important challenges of effective resource management, recovering waste, and optimizing product life cycles. However, it is also important to analyze what kind of advantages circular economy can provide beyond just the environmental ones. These advantages include, but are not limited to, cost savings, differentiation from competitors and even supply chain resilience. Circular economy principles are not just an add-on; they can be successfully integrated with Industry 4.0 practices and technologies to create a more sustainable and cost-effective business model.